If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -8) = 7(x + 2) Reorder the terms: 4(-8 + 2x) = 7(x + 2) (-8 * 4 + 2x * 4) = 7(x + 2) (-32 + 8x) = 7(x + 2) Reorder the terms: -32 + 8x = 7(2 + x) -32 + 8x = (2 * 7 + x * 7) -32 + 8x = (14 + 7x) Solving -32 + 8x = 14 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -32 + 8x + -7x = 14 + 7x + -7x Combine like terms: 8x + -7x = 1x -32 + 1x = 14 + 7x + -7x Combine like terms: 7x + -7x = 0 -32 + 1x = 14 + 0 -32 + 1x = 14 Add '32' to each side of the equation. -32 + 32 + 1x = 14 + 32 Combine like terms: -32 + 32 = 0 0 + 1x = 14 + 32 1x = 14 + 32 Combine like terms: 14 + 32 = 46 1x = 46 Divide each side by '1'. x = 46 Simplifying x = 46
| -17.8s=-17.2s+6.72 | | 3=-m-2m | | Y=(18+.8Y)+24 | | 2.6t=1.5t-8.58 | | 10(v+2)-2v=2(4v+4)-10 | | -3(2)+6-5(2-1)=-5(2)-(2(2)-4)+5 | | 2.3y+y-4=31 | | 7/2x+1-8/2x-1 | | 3x^2-60-3x=0 | | x-19=-1 | | -5=2n-4+1 | | f(x)=8x^2+3x | | 4(2-n)-2=41 | | 3+ab=c | | X+23=51 | | 245=-125(15+p) | | 1.5p+16.98=8.42-7.8p+8.5p | | 8q-(q-4)=3q+4(q+1) | | 1/9x+1/3 | | sqrt(a^2+b^2)=a+b | | 9a+15=10a | | n-14=-14 | | 8m=12(m-1) | | -11x+6=-5x+3 | | 0.70x+0.05(6-x)=0.10(55) | | X+19=46 | | -90=-15x | | 2(m+5)=-25 | | 5-z/2=-9 | | -50x=4.5 | | 34-6b=4(1-8b) | | 273.15=5/9(f-32)+273.15 |